Autologous intrauterine transfusion in a case of anti‐U. Issue 12 (23rd September 2016) - Adam, Sumaiya; Lombaard, Hennie
Abstract : BACKGROUND: Minor red blood cell antibodies are becoming a more common cause of hemolytic disease of the newborn. Anti‐U are a rare alloantibody found almost exclusively in people of black descent. There is limited experience to guide the management of pregnancies complicated by anti‐U. Furthermore, there is often no suitable cross‐matched blood available for transfusion of a patient with anti‐U. CASE REPORT: A 21‐year‐old P0G1 presented at 25 weeks' gestation with D– disease in pregnancy. She had a significant indirect antiglobulin test titer of 512. Anti‐U were identified and no suitable cross‐matched blood was available. Maternal blood was prepared for autologous intrauterine fetal transfusion. Two such transfusions were performed. RESULTS: A healthy fetus delivered at 32 weeks that did not require phototherapy or an exchange transfusion. CONCLUSION: Autologous transfusion of prepared maternal blood provides a safe option for intrauterine fetal therapy in pregnancies complicated by rare alloantibodies.